Sulfidic crosslinks in EPM: a strategy for advanced flexible EPM composites - Parathodika, Arshad Rahman; Naskar, Kinsuk (Frontiers in Soft Matter, 2026)
Ethylene–propylene rubber (EPM) is a fully saturated elastomer, which prevents its crosslinking by conventional accelerated sulfur curing that requires unsaturation. In this study, a hybrid curing approach is introduced to generate sulfidic crosslinks in EPM. The method combines organic peroxide curing with sulfur-based vulcanization. Peroxide generates radicals on the EPM backbone and forms macro radicals, which can be captured by sulfur species, forming sulfur macroradicals that couple either with each other or with other EPM macro radicals to create alkyl-alkyl sulfidic crosslinks in EPM. Alongside these, the system also contains conventional alkyl–alkyl carbon crosslinks generated by peroxide. While carbon–carbon crosslinks impart excellent thermal stability and compression set resistance in EPM, they often limit flexibility and tear strength. The incorporation of sulfidic crosslinks alongside peroxide-derived linkages enhances flexibility and stress strain performance without sacrificing high temperature capability. This hybrid curing route thus provides a promising strategy for developing advanced flexible EPM composites for applications demanding contradictory property requirements and higher thermal ratings than EPDM.